2021
DOI: 10.1111/bph.15459
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapies and their delivery for treating age‐related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the most common cause of blindness in the Western world and is characterised in its latter stages by retinal cell death and neovascularisation and earlier stages with the loss of parainflammatory homeostasis.Patients with neovascular AMD (nAMD) are treated with frequent intraocular injections of anti-vascular endothelial growth factor (VEGF) therapies, which are not only unpopular with patients but carry risks of sight-threatening complications. A minority of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 132 publications
0
18
0
1
Order By: Relevance
“…Currently, intravitreal injection of anti-VEGF drugs is the standard treatment for neovascular ARMD. Patients with neovascular ARMD require long-term repeated intravitreal injections during anti-VEGF therapy [ 4 , 13 ]. Repeated injections may lead to complications such as uveitis, endophthalmitis, subconjunctival haemorrhage, elevated intraocular pressure, retinal detachment, retinal pigment epithelium tears, corneal nerve fibres and sensitivity loss [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, intravitreal injection of anti-VEGF drugs is the standard treatment for neovascular ARMD. Patients with neovascular ARMD require long-term repeated intravitreal injections during anti-VEGF therapy [ 4 , 13 ]. Repeated injections may lead to complications such as uveitis, endophthalmitis, subconjunctival haemorrhage, elevated intraocular pressure, retinal detachment, retinal pigment epithelium tears, corneal nerve fibres and sensitivity loss [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Russ et al have shown that a single topical delivery of GAL-101, a small molecule inhibitor of Aβ, sustained concentrations >100 nm in the retina of monkeys for >2 h. Daily eye drops in a glaucoma rat model achieved >90% neuroprotection [102]. Phase I trials for geographic atrophy have successfully been completed [110].…”
Section: Innovative Small Moleculesmentioning
confidence: 99%
“…In a Phase II trial (NCT01678963), this formulation, with improved trans-scleral permeability and increased choroidal retention, showed a trend towards better visual acuity in patients with all types of naïve neovascular lesions. Subsequent Phase III trials (NCT02727881) failed to meet the primary endpoint [110].…”
Section: Innovative Small Moleculesmentioning
confidence: 99%
“…Two of the articles included in this collection have the impact of ageing on vision as their focus. In their review, ‘emerging therapies and their delivery for treating age‐related macular degeneration’, Thomas et al ( 2022 ) describe age‐related macular degeneration (AMD), the most common cause of blindness in the Western world. With new therapeutic strategies emerging for AMD, novel delivery routes and their implications for translation into clinical practice are critical factors in determining their future success.…”
Section: Linked Articlesmentioning
confidence: 99%